Water Dispersal of Methanotrophic Bacteria Maintains Functional Methane Oxidation in Sphagnum Mosses - Putkinen, Anuliina; Larmola, Tuula; Tuomivirta, Tero; Siljanen, Henri M.; Bodrossy, Levente; Tuittila, Eeva-Stiina; Fritze, Hannu (Frontiers in Microbiology, 2012)
It is known that Sphagnum associated methanotrophy (SAM) changes in relation to the peatland water table (WT) level. After drought, rising WT is able to reactivate SAM. We aimed to reveal whether this reactivation is due to activation of indigenous methane (CH4) oxidizing bacteria (MOB) already present in the mosses or to MOB present in water. This was tested through two approaches: In a transplantation experiment, Sphagna lacking SAM activity were transplanted into flark water next to Sphagna oxidizing CH4. Already after 3 d, most of the transplants showed CH4 oxidation activity. Microarray showed that the MOB community compositions of the transplants and the original active mosses had become more similar within 28 d thus indicating MOB movement through water between mosses. Methylocystis-related type II MOB dominated the community. In a following experiment, SAM inactive mosses were bathed overnight in non-sterile and sterile-filtered SAM active site flark water. Only mosses bathed with non-sterile flark water became SAM active, which was also shown by the pmoA copy number increase of over 60 times. Thus, it was evident that MOB present in the water can colonize Sphagnum mosses. This colonization could act as a resilience mechanism for peatland CH4 dynamics by allowing the re-emergence of CH4 oxidation activity in Sphagnum.